2022
DOI: 10.3390/horticulturae8040342
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Infrared Postharvest Treatment of Barhi Dates Using Response Surface Methodology (RSM)

Abstract: Barhi dates are widely consumed at Khalal maturity stage and preserving the freshness quality of Barhi at this stage is a challenging task as this period is short and the fruits are more perishable. In this study, response surface methodology (RSM) was applied to optimize the infrared (IR) treatment and storage conditions for preserving the physicochemical, microbial, and bioactive attributes of fresh Barhi dates. The effect of four factors, IR temperature (50, 70, 90, and 110 °C), IR time (1, 2, 3, and 4 min)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…The high coefficients of determination (R 2 ) were observed for TSS, firmness, ∆E, TVC, TPC, DPPH, glucose, and fructose, which were ranged from 0.925 to 0.992, suggesting that the applied quadratic polynomial models (Equation (9)) contributed to more than 92% of the total variability of traits. Similar observations were recently reported for Barhi dates treated with infrared at different doses and duration and storage at different temperature and times [ 15 ]. Comparable results of coefficients of determination (R 2 ), predicted R 2 and adjusted R 2 indicate a good statistical model [ 16 ].…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The high coefficients of determination (R 2 ) were observed for TSS, firmness, ∆E, TVC, TPC, DPPH, glucose, and fructose, which were ranged from 0.925 to 0.992, suggesting that the applied quadratic polynomial models (Equation (9)) contributed to more than 92% of the total variability of traits. Similar observations were recently reported for Barhi dates treated with infrared at different doses and duration and storage at different temperature and times [ 15 ]. Comparable results of coefficients of determination (R 2 ), predicted R 2 and adjusted R 2 indicate a good statistical model [ 16 ].…”
Section: Resultssupporting
confidence: 90%
“…Comparable results of coefficients of determination (R 2 ), predicted R 2 and adjusted R 2 indicate a good statistical model [ 16 ]. The current results showed that adjusted R 2 of the assessed attributes were in the range of 0.871 to 0.958, which was comparable to that of R 2 (0.925 to 0.992) indicating high significance of the applied model that is similar to our recent observations on RSM model used for optimizing infrared treatment of Barhi dates [ 15 ]. In addition, the coefficient results also indicated high correlations between predicted and actual values of TPC, TSS, firmness, DPPH, ∆E, TVC, glucose, and fructose because the coefficient values (R 2 and adjusted R 2 ) were near to one [ 16 , 17 ].…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations